The Use Of Junior High School Social Studies Teaching Materials Containing Multicultural Life Material In Singkawang City - Karel Juniardi; Aim Abdulkarim; Elly Malihah; Erlina Wiyanarti (STKIP Singkawang, 2024)
This research is entitled The Use of Middle School Social Sciences Teaching Materials Containing Multicultural Life Material in Singkawang City. This research aims to find out what form of social studies teaching materials are used in junior high school social studies learning in Singkawang City and what the material content of multicultural life in Singkawang City is in the social studies teaching materials used by teachers in junior high school social studies learning in Singkawang City. This research uses qualitative methods with data collection techniques using interview techniques, observation and document analysis at 5 junior high schools in Singkawang City. The validity of the data used is data triangulation and method triangulation. Meanwhile, the data analysis technique uses interactive analysis with three stages of analysis, namely data reduction, data presentation, and drawing verification conclusions. The research results show that, first, the form of social studies teaching materials used by teachers in learning social studies in class VIII of junior high schools in Singkawang City is printed teaching materials in the form of books, namely social studies textbooks or student books published by the government and worksheet books that refer to the Merdeka Curriculum. Second, in the social studies teaching materials used by teachers in learning social studies in class VIII of junior high schools in Singkawang City, there is no material content about multicultural life in Singkawang City. The material content in the social studies teaching materials used by teachers in junior high school social studies learning in Singkawang City only contains national or general social studies material, so to get around the absence of material content on multicultural life in Singkawang City in junior high school social studies teaching materials, the teacher conveys multicultural life material in Singkawang City is given verbally in a limited manner according to the teacher’s knowledge. Thus, it is necessary to recommend the development of teaching materials based on multicultural life in Singkawang City in junior high school social studies learning in Singkawang City as a means of multicultural education so that students become more acquainted with know and understand the social life and cultural traditions that exist in the environment around which students live with the hope that students can discover, appreciate and apply social values in multicultural life in Singkawang City which are the basis for building students’ social attitudes in order to create a harmonious and tolerant social life in Singkawang City.